PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MEDIA VIDEO ANIMASI PADA PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SEKOLAH KHUSUS NURASIH CIPUTAT TANGERANG SELATAN - Kirana, Andi Ade Diandra; Diah Mutiara (STKIP Subang, 2026)
This study examines the implementation of Islamic Religious Education (PAI) learning through the use of animated video media for students with special needs at Sekolah Khusus Nurasih Ciputat, Tangerang Selatan. The background of this research is based on the low effectiveness of conventional teaching methods, especially lectures, which are less able to attract attention and facilitate understanding for students with cognitive and attention limitations. Therefore, innovative and adaptive learning media are needed, one of which is animated video. This research aims to describe the planning, implementation, and evaluation of PAI learning through animated video media. This study uses a qualitative approach with a descriptive method. Data were obtained from the principal and PAI teachers as primary sources, while documentation served as secondary data. Data collection techniques included observation, interviews, and documentation, with data analysis conducted through data reduction, data presentation, and conclusion drawing, as well as data validation through triangulation techniques. The results show that: (1) learning planning is adjusted to the characteristics of students with special needs and learning objectives; (2) the implementation of animated video media increases students' attention, interest, and understanding due to its visual and concrete presentation; and (3) evaluation emphasizes not only cognitive aspects but also affective and psychomotor aspects tailored to students' abilities. Thus, the use of animated video media has a positive impact on the learning process and outcomes of students with special needs.